Impact of the type of anesthesia on the frequency of postoperative complications after hernioplasty and on the dynamics of the frailty index in elderly patients with inguinal hernia - B. D. Akhverdiev (Исследования и практика в медицине)
Purpose of the study. The purpose of the study was to compare the eﬀect of spinal and general anesthesia on the incidence of postoperative complications aﬅer hernioplasty and on the dynamics of the frailty index (FI) in elderly patients with inguinal hernia.Patients and methods. 78 patients diagnosed with inguinal hernia were involved in the study (average age was 70.1 ± 0.8 years). Patients underwent open hernia repair and Lichtenstein plasty of the posterior wall of the inguinal canal. The patients were divided into two groups depending on the type of anesthesia: spinal anesthesia (SA; N = 65) and general anesthesia (GA; N = 13). At the time of admission, 30 days aﬅer the surgery, the FI was calculated using the Edmonton questionnaire.Results. In the SA group, 39 patients (60 %) had a FI ≥ 7; 9 patients (13.8 %) had a FI ≥ 9; 8 patients (12.3 %) had a FI ≥ 11; and 9 patients (13.8 %) had the highest FI ≥ 12. At 30 days aﬅer surgery, 20 patients (30.8 %) showed a decrease in FI values (FI from 7 to 9 decreased almost 2-fold). In the GA group, on the day of admission, 6 patients (46.2 %) had FI ≥ 7, 5 (38.5 %) had FI ≥ 9, and 2 (15.4 %) had FI ≥ 11. At 30 days aﬅer surgery, no changes were observed in patients with FI ≥ 7.Conclusion. In the spinal anesthesia group, urinary retention was predominant among complications, while in patients aﬅer general anesthesia, pulmonary atelectasis prevailed among complications. The use of spinal anesthesia for hernioplasty was accompanied by a decrease in the frailty index within 30 days aﬅer surgery in individuals with a FI ≥ 7. In the GA group, decrease in the index within 30 days aﬅer surgery was observed in patients with FI ≥ 9.